Synthesis, structural, magnetic and phase-transition studies of the ferromagnetic La2CoMnO6 double perovskite by symmetry-adapted modes. Issue 31 (21st August 2015) - Orayech, B.; Urcelay-Olabarria, I.; López, G. A.; Fabelo, O.; Faik, A.; Igartua, J. M.
<x xml:space="preserve">Abstract</x> A powdered La2CoMnO6 double perovskite was synthesized by the solid-state reaction method, and its crystal structure and phase-transitions were investigated by (Mode Crystallography) Rietveld analysis using X-ray and neutron diffraction data. Three indistinguishable ferromagnetic models with the space groups P21/n and P2′1/n′ are proposed.